What is the value of asset management?. Issue 2 (7th January 2019) - Woodhouse, John
Abstract : This paper summarises and clarifies the different perceptions of value and benefits associated with assets and their life cycle management. It seeks a common ground in the terminology and practical measurement or demonstration of impact for the varied audience of financial, technical and regulatory stakeholders, customers and other interest groups. It also illustrates some of the reported benefits (added value) being achieved by (better) asset management, such as those being generated through the introduction of PAS 55 or ISO 55000 standards.